Fossils of All Kinds : Digested into a Method, Suitable to their Mutual Relation and Affinity - Woodward, John, 1665-1728 (Place of publication not identified : publisher not identified, 1728)
To the naturalist John Woodward (c.1665-1728), fossils were'much neglected, and left wholly to the Care and Treatment of Miners and meer Mechanicks'. He had built up a large personal collection of these samples of the Earth's petrified remains and spent much of his life developing a system for their classification, the results of which were published in this important illustrated work of 1728. A distinguished physician and a fellow of the Royal Society, Woodward wrote extensively on scientific topics, and had developed a theory that fossils were creatures destroyed in the flood described in the Bible. These ideas attracted critics and supporters in equal measure, but his contribution to techniques of fossil collection and classification were influential. In the present work, he devotes the early chapters to questions of description and classification, while the later sections contain some of his letters to his scientific contemporaries, including Isaac Newton.
Includes indexes.
Keywords: Fossils -- Early works to 1800.